Identification of polymer matrix yield stress in the wood cell wall based on micropillar compression and micromechanical modelling. Issue 32 (1st December 2016) - Schwiedrzik, Jakob; Raghavan, Rejin; Rüggeberg, Markus; Hansen, Silla; Wehrs, Juri; Adusumalli, Ramesh B.; Zimmermann, Tanja; Michler, Johann
Abstract : Based on a combination of micropillar compression experiments and modelling of the secondary cell wall (cw) using continuum micromechanics, the shear yield stress of the polymer matrix is identified for both normal and compression wood of Norway spruce. It is shown that the model is able to capture the differences in mechanical properties between the two tissues based on the knowledge of composition of the samples, microfibril angle, as well as phase properties on the nanometer scale. By testing an isolated piece of the cell wall with a homogeneous and uniaxial stress field on the micrometer scale and using the micromechanical model to determine average stress fields on the nanometer scale, it is possible to identify the shear yield stress of the polymer matrix in wood, which was found to be in the range of 14.9–17.5 MPa for normal and compression wood. It was shown that this corresponds to a stress in the lignin phase of approx. 17 MPa. This combined study thus demonstrates a new approach for validating multiscale models predicting yield properties with uniaxial experiments at the microscale and measuring phase properties of inhomogeneous materials by a combination of modelling and experimental approaches.